If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8r + 3s = 0 Solving 8r + 3s = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3s' to each side of the equation. 8r + 3s + -3s = 0 + -3s Combine like terms: 3s + -3s = 0 8r + 0 = 0 + -3s 8r = 0 + -3s Remove the zero: 8r = -3s Divide each side by '8'. r = -0.375s Simplifying r = -0.375s
| 3(3.25+-0.6666666667b)=9.75 | | 3(3.25+-0.6666666667b)=975 | | 3x^2-2x+0=0 | | b-7whenb=17 | | x=-16-186 | | -4+15j=8j+7j-4 | | 3b-5=8b-20 | | 3a+2b=9.75 | | 2-6g=11-3g | | 2x-2=x+17 | | r^4+8r^2-16=0 | | 18x^2+12x+22=18x^2+24x+8 | | 2h+5h=7h | | 15+n=m | | -2x-13+-8x+13=90 | | 6x+9=5x-12 | | 5d=5d+4 | | 16+6x=8y | | -9(x-6)-6=48 | | -y+2x=24 | | 4x=9x+54-2 | | -3+4f=10+4f | | K+2=5k+10 | | x+3y+4z=-4 | | 5a=2a+3 | | -3y-1=-1-3y | | 16+8x=8y | | 50-(3x+10)= | | -3+8-6t=-6t+5 | | -4-3x=-10-4k | | 3a-(8-6b)= | | -8-8m=-8m-8 |